2014
DOI: 10.1016/j.toxlet.2013.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Melanocytes and keratinocytes have distinct and shared responses to ultraviolet radiation and arsenic

Abstract: The rise of melanoma incidence in the United States is a growing public health concern. A limited number of epidemiology studies suggest an association between arsenic levels and melanoma risk. Arsenic acts as a co-carcinogen with ultraviolet radiation (UVR) for the development of squamous cell carcinoma and proposed mechanisms include generation of oxidative stress by arsenic and UVR and inhibition of UVR-induced DNA repair by arsenic. In this study, we investigate similarities and differences in response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…a,b). At higher UVB doses such as 30 or 40 mJ/cm 2 , however, we found that UVB had less impact on the viability of melanocytes than on keratinocytes, consistent with previous observations . While melanin produced by melanocytes is widely known to confer protection against UVR in skin cells , the molecular mechanism(s) underlying melanocyte resistance to UVB have not been clearly defined.…”
Section: Resultssupporting
confidence: 89%
“…a,b). At higher UVB doses such as 30 or 40 mJ/cm 2 , however, we found that UVB had less impact on the viability of melanocytes than on keratinocytes, consistent with previous observations . While melanin produced by melanocytes is widely known to confer protection against UVR in skin cells , the molecular mechanism(s) underlying melanocyte resistance to UVB have not been clearly defined.…”
Section: Resultssupporting
confidence: 89%
“…Oxidative stress is thought to be involved in HQ‐induced apoptosis . The formation of reactive oxygen species (ROS) activates the caspase‐dependent pathway of apoptosis and a variety of endogenous ROS immediately activate PARP‐1 to repair DNA damage in melanocytes . To explore whether and how the PARP‐1 pathway is involved in HQ‐induced cell cycle arrest and apoptosis, we generated cell line with depletion of PARP‐1 using RNA interference (RNAi) and investigated the role of PARP‐1 in HQ‐mediated cell cycle arrest and apoptosis with a particular emphasis on the correlations between PARP‐1, caspase‐3 activation, and p53‐mediated cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Melanocytes are more resistant to UV induced cytotoxicity than are keratinocytes, the epidermal skin cells responsible for most non-melanoma skin cancers. This difference may explain the observation that arsenic increases the cancer incidence of non-melanoma skin cancers [86] while the relationship between arsenic and melanoma development is less clearly established [87, 88]. Since deficiencies in the removal of BPDE adducts or UV-induced photolesions by NER result in increased mutation levels, the inhibition of NER by arsenite could explain how arsenic can act as a co-carcinogen in smoking-related lung and UV-related skin cancers.…”
Section: Discussionmentioning
confidence: 99%